Analisis Bentuk Kekerasan Seksual di Lingkungan Sekolah Dasar Pada SDN PANDIAN 1 - Rofiqi, Ahmad Zaki; Zainuddin, Zainuddin; Sukitman, Tri (CV. Ulil Albab Corp, 2025)
Sexsual violence is an act that violates moral and legal norms and has a negative impact on the victim, both physically and psychologically. This study aims to understand the phenomenon of sexual violence that occurs in elementary school environments, especially at SDN Pandian 1. Based on observations, it was found that sexual violence in verbal and non-verbal forms still often occurs, both by fellow students and other parties in the school environment. This study uses a qualitative method with observation, interview, and documentation approaches. The results of the study showed that verbal sexual violence, such as insults and derogatory remarks, often occurred among students. Meanwhile, non-verbal sexual violence, including inappropriate touching, was also found in some cases involving students and external parties. Cases Sexual violence in elementary schools does not only occur at SDN Pandian 1 but also in various other regions in Indonesia, as recorded in several previous studies. Psychological and environmental factors are the main causes of these actions. Therefore, more systematic prevention efforts are needed, including the active role of teachers, schools, and the community in increasing awareness and providing protection for children in the educational environment.